Angiotensin II inhibitor facilitates epidermal wound regeneration in diabetic mice - Kamber, Maria; Papalazarou, Vasileios; Rouni, Georgia; Papageorgopoulou, Evagelia; Papalois, Apostolos; Kostourou, Vassiliki (Frontiers in Physiology, 2015)
Tissue regeneration and wound healing are severely impaired in diabetes and are associated with poor circulation and dysfunctional blood vessels. Angiotensin II inhibitors are anti-hypertensive drugs used in clinical practice to regulate blood pressure and could affect tissue remodeling. We hypothesize that blocking angiotensin II, using Losartan, could facilitate tissue regeneration in diabetic mice. To this end, we established an experimental model of wound healing in streptozotocin-induced diabetic mice. Our data demonstrated that Losartan accelerates wound repair and normalizes wound stromal responses, having a beneficial role in diabetic wounds. Our findings highlight a potential therapeutic use of Losartan in improving wound repair in diabetic conditions.